PENGEMBANGAN PENERAPAN SISTEM PARKIR MENGGUNAKAN BARCODE BERBASIS CLIENT SERVER PADA INFORMATICS AND BUSINESS INSTITUTE IBI DARMAJAYA - hendra kurniawan (IIB Darmajaya, 2011)
Parking system is a step in regulating the rate of development of vehicles that will park in IBI Darmajaya Bandar Lampung, hope that this parking system can be utilized to facilitate the control of data on IBI Darmajaya parking Bandar Lampung. The method used in the manufacture of this data processing system is the method of the System Development Life Cycle (SDLC) model of Waterfall. And data collection performed by the method of observation and book study while the implementation of this waterfall models described by systems analysis, Data Flow Diagram, Normalization, Table Structure Database, Table Relationships, and the design of Input / Output. To design and create a data processing system, the use Borland Delphi 7.0, and Microsoft SQL Server as the database. Keywords : Parking System, Barcode, Waterfall.